2009
DOI: 10.1007/s00270-009-9743-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Transjugular and Plugged-Percutaneous Liver Biopsy in Patients with Contraindications to Ordinary Percutaneous Liver Biopsy and an “In-House” Protocol for Selecting the Procedure of Choice

Abstract: The purpose of this study was to evaluate the effectiveness and safety of transjugular liver biopsy (TJLB) and plugged-percutaneous liver biopsy (PB) in consecutive patients with severe liver disease associated with impaired coagulation, ascites, or both and to verify the in-house protocol used to select the appropriate procedure. In 2000-2006, 329 patients (208 male [62.8%] and 121 female [37.2%]), aged 1 month to 81 years (mean, 46.8 years), underwent 150 TJLBs (39.1%) or 233 PBs (60.9%) procedures at a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…An unfavorable HV angle with respect to the IVC has been the major limitation of TJLB, and it has been cited as the main cause of failed TJLB . However, we found that transfemoral liver biopsy with a Quick‐Core biopsy needle was feasible and safe for select LDLT recipients.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…An unfavorable HV angle with respect to the IVC has been the major limitation of TJLB, and it has been cited as the main cause of failed TJLB . However, we found that transfemoral liver biopsy with a Quick‐Core biopsy needle was feasible and safe for select LDLT recipients.…”
Section: Discussionmentioning
confidence: 72%
“…Liver biopsy is sometimes required to exclude rejection, infection, or other pathologies after living donor liver transplantation (LDLT), and transjugular liver biopsy (TJLB) is usually recommended for patients with uncorrectable coagulopathy, thrombocytopenia, or ascites . Although TJLB is associated with a significant financial burden, TJLB is also used in liver transplant recipients because of its reduced risk of bleeding and the possibility of evaluating the hepatic venous pressure gradient and outflow .…”
mentioning
confidence: 99%
“…In the past, transjugular liver biopsy had been advocated in patients with bleeding diathesis, massive ascites, and poor respiratory control. 7,8 However, this has multiple disadvantages. In particular, it is not feasible for liver lesions far from the major hepatic veins.…”
Section: Discussionmentioning
confidence: 99%
“…Plugged percutaneous biopsy is an alternative to transjugular liver biopsy in patients at high risk of bleeding. 2,8,13 It was first described by Riley et al in 1984. 13 In plugged biopsy, the tract is embolised (plugged) after the percutaneous biopsy, thus decreasing the risk of haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few comparative studies between transjugular and percutaneous biopsy was reported in 1994 by Hong-Chaing Meng et al In this study the complication rate for the transjugular route was 7% and 9% for the percutaneous route suggesting that transjugular biopsy was at least as safe as percutaneous liver biopsy and re-affirmed the idea that it is a safe alternative in patients in whom percutaneous biopsy is contra-indicated. Interestingly, Atar et al reported a comparative study of plugged percutaneous liver biopsy and transjugular biopsy and found no difference in major complications in either group (Atar, et al 2010). They suggested that the plugged percutaneous biopsy technique should be used instead of the transjugular route when available.…”
Section: Transvenous Liver Biopsymentioning
confidence: 99%